Relevansi Pemikiran Pendidikan Kristen Robert Raikers terhadap Pembinaan Karakter Anak di Sekolah Minggu - Yakub Fransisko; Sirnawati Sirnawati; Roberth Jekson Msiren; Sarmauli Sarmauli (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to analyze the relevance of Robert Raikes' Christian educational thinking to the character formation of children in contemporary Sunday School services. This study uses a qualitative approach with a library research method. Data were obtained from various literature sources such as books, scientific journals, and research articles related to Christian education, character education, and the history of Sunday School development. Data analysis techniques were carried out through the stages of data reduction, grouping themes, interpretation, and drawing conclusions using descriptive qualitative methods. The results show that Robert Raikes' thoughts remain relevant in modern Christian education, especially in the formation of children's character through the teaching of God's Word, discipline, role models, and the instilling of Christian values. Sunday School plays an important role as a means of fostering faith, morality, and social responsibility in children from an early age. In addition, the challenges of the digital era require churches to develop more creative, interactive, and contextual learning methods without abandoning the basic values ​​of the Christian faith. This study confirms that the success of children's character formation depends not only on the church, but also on the role of Sunday School teachers and families who work together to build a conducive spiritual environment. Thus, Robert Raikes' thinking makes an important contribution to the development of Christian education that is relevant in the modern era.